(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
The study was conducted to investigate the improvement achieved through the treatment of two tomato varieties (ANSAL and Dan-Zaria) with Alpha-Spin® nanoparticles in a screenhouse at Jauro Yinu in Ardo-Kola LGA, Taraba State, Nigeria. Seeds were exposed to the Alpha-Spin® nanoparticles® for durations of 15, 30, 45, and 60 minutes before planting, using a Randomized Complete Block Design with a control group. The results of data collected and analyzed using GENSTAT statistical software showed that Alpha-Spin® treatments did not affect germination time (which was 7 days after planting for ANSAL and 3 days for Dan-Zaria in all exposures) or plant height (Dan-Zaria: 148.33 cm). However, it significantly improved other growth parameters, including stem girth (Dan-Zaria: 19.33 mm), number of branches (Dan-Zaria: 11), flowering time (27 days after transplanting for Dan-Zaria and 31 days for ANSAL with 15 minutes exposure), and number of flower clusters (ANSAL: 37). Overall, Dan-Zaria exhibited better growth than ANSAL in most of the growth parameters. These results indicate that exposure to Alphaspin® nanoparticles enhanced the growth parameters like stem girth, number of branches per plant, and days to 50% growth) in tomato varieties, making it a recommended treatment for trait improvement in tomato breeding programs.